2020
DOI: 10.1101/2020.05.02.20088500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Changes in soluble CD163 indicate monocyte involvement in cognitive deficits in Parkinson’s disease”

Abstract: Parkinson's disease is a neurodegenerative disorder with a significant immune component. Numerous studies have reported alterations on immune biomarkers in CSF and serum that associate with symptoms in PD patients. However, it is unclear, which specific immune cells are responsible for the changes in those biomarkers; since most of these cytokines or chemokines, can be produced by a variety of immune cells, or even neurons or glia cells in the brain. Here, we investigate a monocyte/macrophage-specific biomarke… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 95 publications
(190 reference statements)
1
9
0
Order By: Relevance
“…We and others have shown that MNP-associated changes seem particularly relevant for cognition in PD (26, 37, 40). Elevated CCR2 expression is a signature of newly-generated immature Mos from the bone marrow, marked for migration to blood and tissue.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…We and others have shown that MNP-associated changes seem particularly relevant for cognition in PD (26, 37, 40). Elevated CCR2 expression is a signature of newly-generated immature Mos from the bone marrow, marked for migration to blood and tissue.…”
Section: Discussionmentioning
confidence: 73%
“…In HCs, plasma sCD163 correlates negatively with CD163 MFI, but not with CD163 + cell counts (64). With our previous finding of increased serum sCD163 levels in females with PD (26), we anticipated a decrease in CD163 MFI on MNPs from females with PD. However, we observed a significant increased CD163 MFI in PwP for both sexes, indicating a PD-associated upregulation of CD163, in parallel to the increased shedding observed in serum (in females) and CSF (both sexes) (26).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations